Effects of cutting frequency and cutting height on reserve carbohydrates in gliricidia sepium (Jacq.) Walp. - Erdmann, T.K.; Nair, P.K.R.; Kang, B.T. (1993)
This study examined the effects of cutting frequency and cutting height on reserve carbohydrates in Gliricidia sepium, a multipurpose woody perennial used widely in tropical agroforestry systems. Sample cores of major lateral roots and lower stems, taken from plant cut at 3- and 6-week intervals and from uncut (control) plants, as well as plants that were cut at 0, 25 and 100 cm above the ground, were analyzed for soluble sugars and starch using the perchloric acid method. Results indicate that G. sepium used stem starch to support initial coppice shoot growth after cutting and that this carbohydrate fraction was present in sufficient concentrations to preclude use of root reserve carbohydrates. Evidence obtained also supported the hypothesis that deciduous trees in the seasonally dry tropics accumulate reserve carbohydrates early in the dry season.